APPLICATION OF OILY PIG-IRON SHAVING FOR REPLACEMENT OF AN EXPENSIVE AND DEFICIT SCRAP - A. I. Garost (Литьë и металлургия)
The results of researches on creation of the cast iron melting technology using iron-containing materials with organic contaminants as burden are given.